PEROLEHAN DAN PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMBELAJARAN PROBLEM POSING DAN DIRECT INSTRUCTION DITINJAU DARI SELF EFFICACY SISWA - Sri Winggowati, Winggo (2023)
This study aims to analyze and describe the effect of problem-posing (PP) and direct instruction (DI) learning on the acquisition and improvement of students' mathematical communication skills (KKM) in terms of the level of students' mathematical self-efficacy (SE), as well as obtain a conjecture that relates the level of SE students with KKM in solving comparison questions. The method used in this research is a mixed method of explanatory sequential design with quantitative and qualitative stages. In the quantitative stage, descriptive and quasi-experimental research was used with a 3x2 factorial design. In the qualitative stage, a case study design is used with a grounded theory perspective and systematic procedures. The sample in this study was 5th-grade students of public elementary schools in the city of Bandung, totaling 84 students. From this study, the following conclusions were obtained: i) Learning with the PP and DI models each had a significant effect on students' KKM acquisition. ii) There is no interaction effect between learning and SE level on the acquisition and improvement of students' KKM. iii) The implementation of PP learning has a higher effect than DI model learning on KKM acquisition. iv) There is no interaction effect between learning and the level of SE on the improvement of students' KKM. v) Student SE has a positive effect on students' KKM. vi) KKM students who have a high SE level can communicate symbols and visuals (visualization, representation), communicate concepts (mathematical ideas, language, concepts, and examples), build arguments (arguments and evidences), and discuss and collaborate mathematically (discussions, listening to arguments, collaborative)